Opportunities and Barriers Against Successive Implementation of Rainwater Harvesting Options to Ensure Water Security in Southwestern Coastal Region of Bangladesh - Afsari, Navila; Murshed, Sonia Binte; Uddin, Sayed Mohammad Nazim; Hasan, Monzurul (Frontiers in Water, 2022)
Safe drinking water scarcity is an acute problem in the coastal regions of Bangladesh. Salinity intrusion in freshwater bodies, arsenic contamination, and low dry season rainfall are some of the reasons behind this deplorable condition. Such is the case in a southwestern district, Satkhira, where safe drinking water is a mirage for people. In this situation, Rainwater Harvesting (RWH) and its utilization could be an environmentally sound solution among the various technologies to augment freshwater resources. RWH is increasingly becoming an integral part of the sustainable water management toolkit. However, some issues are hindering the success of RWH. The absence of technical knowledge, unawareness of the hygiene, economic constraints, and lack of training program on the usage and maintenance of the technology are major reasons for reducing RWH technology's acceptability. This study assessed existing RWHs from several locations of Shyamnagar Upazila of Shatkhira district, incorporating social, economic, and institutional aspects along with policy and application gaps. A mixed-method approach was adopted for the assessment, which included 20 site inspections, questionnaire surveys among the consumers, focus groups discussions with concerning stakeholders, key informant interviews with local government officials. From the outcomes, Strength Weakness Opportunity Threat (SWOT) analysis was done to conduct a baseline assessment of existing RWH opportunities and implementation constraints. We identified RWH as the most appropriate supplementary water source in this region. The substantial factors which enhanced the use of RWH in the study area were the proximity of water in comparison to alternative water sources, the potential for improved livelihoods, protection against climate unpredictability, and support from local government and Non-Government Organizations. Furthermore, there was enough quantity of water to support the total water need in household activities. However, a lack of awareness and financing mechanisms were identified as significant social barriers to RWH use. There is a significant gap between policy and implementation at the field level. Identifying the drivers, barriers, and outcomes of RWH use in the study area allows policymakers and water practitioners to understand better which incentives, programs, and mechanisms can support the sustainable implementation of RWH in Bangladesh.